PENDETA SEBAGAI MOTIVATOR KEAKTIFAN PEMUDA DALAM IBADAH DI GMIH MALADOM: TINJAUAN KEPEMIMPINAN TRANSFORMASIONAL - Bernadus, Petran Nazario; Tampake, Tony Robert Christian; Suprabowo, Gunawan Yuli Agung (SEKOLAH TINGGI TEOLOGI INJILI SETIA SIAU, 2024)
Youth is the backbone and the next generation that brings new vision, spirit, and energy in carrying out the mission of the church. However, in church life, youth often face challenges of inactivity in worship and service. The congregation of GMIH Maladom in Porniti Village, Central Jailolo, West Halmahera, North Maluku, also faces this problem. This study aims to analyze the pastor's role as a motivator of youth activeness in worship in terms of transformational leadership. The research used qualitative-descriptive method with observation and interview techniques. The selection of sources was carried out using purposive sampling technique and the research data was analyzed using phenomenological analysis techniques. The results showed that the pastor's leadership in GMIH Maladom congregation can be identified as transformational leadership. Pastors motivate youth by providing vision, creating personal closeness, providing spiritual guidance, giving responsibility, and giving appreciation. This leadership results in positive changes in youth participation in church worship and service. The findings suggest that pastors with a transformational leadership approach can be effective motivators in mobilizing youth to be active in the church.